ADSORPTION STUDY OF CRYSTAL VIOLET USING NATURAL ZEOLITE OF INDONESIA - Hasanah, Aulia
Liquid dye waste is one that can cause environmental damage from the textile industry. One of them is Crystal Violet (CV) dye waste which is a dye that is often used as a dye in the textile industry, veterinary medicine, dermatology and is used as a Gram stain for microorganism markers. CV can be teratogenic (causing defects in the fetus during pregnancy), carcinogenic (cancer-causing) and mutagenic (gene mutation) so that it poses a serious threat to human health. Therefore, it is necessary to make efforts to reduce the amount of CV in dye waste. One way is to use adsorption techniques. The adsorbent used was Ende natural zeolite, which is known to have the main composition of mordenite, clinoptilolite and quartz. Natural zeolite adsorbents were then tested in three conditions, namely, 100mesh size, nano modification with planetary milling using alumina balls (200 rpm/12 hours), and with recrystallization. Adsorbents were characterized using X- Ray Florescence (XRF), Fourier Transform Infra Red Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD). Optimum conditions for CV adsorption using 0.01 gram of adsorbent were achieved at pH 6 and a contact time of 90 minutes using a volume of 10 mL solution, with the batch method. The CV adsorption process followed the pseudo second order adsorption kinetics model and the Langmuir isotherm model with a maximum adsorption capacity of 151.327 mg/g and an R2 value = 0.9635 for sample A, 74.166 mg/g and an R2 value = 0.9128 for sample B, and a capacity the maximum adsorption was 311.357 mg/g and the R2 value = 0.9752 for sample C. The thermodynamic study of the three sample conditions yielded a negative ?G value indicating that the process was spontaneous, endothermic with positive ?H values and positive ?S indicating that the degree of orderliness of the system increased